2020
DOI: 10.1177/1078155220953877
|View full text |Cite
|
Sign up to set email alerts
|

Alternative use of BRAF inhibitors in patients with metastatic melanoma unable to swallow pills

Abstract: Introduction BRAF and MEK inhibitors have been approved for use in metastatic melanoma therapies. All of them are administered as oral capsules or pills. We report two cases treated applying an alternative method of vemurafenib or debrafenib-trametinib administration in patients unable to swallow. Case Report The first case involved a 38-year-old man who was referred to a dermatologist for dysphagia and anorexia. After a computerized tomography (CT) scan it was concluded that the dysphagia was due to compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Review of agents found 36 (31%) with guidance for alternative routes of administration readily available in tertiary resources or commercial liquid formulations, 38 (33%) with off‐label manufacturer information or case reports describing manipulation of solid dosage formulations, and 42 (36%) with no data or insight limited to pharmacokinetic studies. Findings are detailed in Table 3 10‐196 . Unique administration instructions (ie, with or without foo...…”
Section: Resultsmentioning
confidence: 99%
“…Review of agents found 36 (31%) with guidance for alternative routes of administration readily available in tertiary resources or commercial liquid formulations, 38 (33%) with off‐label manufacturer information or case reports describing manipulation of solid dosage formulations, and 42 (36%) with no data or insight limited to pharmacokinetic studies. Findings are detailed in Table 3 10‐196 . Unique administration instructions (ie, with or without foo...…”
Section: Resultsmentioning
confidence: 99%